ISLAMIC ECONOMICS AND THE CLIMATE CRISIS: RECONSTRUCTING THE ROLES OF ZAKAT AND WAQF IN ACHIEVING ENVIRONMENTAL RESILIENCE - Abrar, Muhammad; Putra, Zulfan Adi; Ihza, Muhammad Herizal (Proceedings of Aceh International Seminar on Zakat and Waqf, 2026)
The global climate crisis demands responses from various sectors, including Islamic economics, which holds significant potential in supporting environmental sustainability through social instruments such as zakat and waqf. This study aims to explore the relevance and contribution of Islamic economic approaches in addressing contemporary ecological challenges. Using a literature review method based on five key studies, the findings reveal that: (1) Islamic economic approaches are urgently needed in climate crisis response policies; (2) the function of zakat must be reconstructed to enhance environmental resilience; (3) productive waqf can be recontextualized as an ecological instrument; (4) the integration of zakat and waqf contributes to the development of an Islamic green economic model; and (5) digitalization and social innovation play a strategic role in optimizing zakat and waqf for environmental purposes. These findings indicate that zakat and waqf are not only social and economic tools but also hold ecological value that can be maximized through cross-sector collaboration and digital technology. The study recommends strengthening regulations, enhancing institutional synergies, and developing green zakat and eco-waqf programs as adaptive strategies in addressing climate change.